"Bartlett Bemister" - Rorke Family (1880)
George Bartlett Bemister. George Bartlett Bemister (1845-1932), eldest son of Captain Willis Bemister and Mary Elizabeth (Bartlett) Bemister, was born at Carbonear on 26 May 1845. He married Mary Elizabeth ''Lizzie'' McPhilliips at St. Charles, Manitoba on 9 February 1874. They had 13 children. He died at Winnipeg, Manitoba on 22 May 1932. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.